Commercial bank behavior and economic activity : a structural study of monetary policy in the postwar United States - Goldfeld, Stephen M. (Amsterdam : North-Holland Publishing, 1966)
This study presents an aggregate quarterly model of the postwar United States economy. The primary aims in constructing the model are: to examine commercial bank portfolio behaviour; to relate investment and consumption expenditures directly to financial variables; and to investigate the impact of monetary policy on both financial and non-financial variables
Includes bibliographical references and index
osc 15/01/2019
Loans
Keywords: Banks and banking; Monetary policy; Currency question